2018
DOI: 10.1007/s00213-018-4949-x
|View full text |Cite
|
Sign up to set email alerts
|

Dl-3-n-Butylphthalide improves lipopolysaccharide-induced depressive-like behavior in rats: involvement of Nrf2 and NF-κB pathways

Abstract: These results provide more insight into pathogenesis of MDD and firstly demonstrated the potential antidepressant actions of NBP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 52 publications
4
40
0
Order By: Relevance
“…An increasing number of studies have suggested that inflammation plays a crucial role in the process of MDD (Rush et al, 2016;Yang M. et al, 2018). The activation of microglia, a kind of macrophage in the brain, can trigger the expression of proinflammatory cytokines involved in the pathological development of neuroinflammation-and degeneration-related diseases.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…An increasing number of studies have suggested that inflammation plays a crucial role in the process of MDD (Rush et al, 2016;Yang M. et al, 2018). The activation of microglia, a kind of macrophage in the brain, can trigger the expression of proinflammatory cytokines involved in the pathological development of neuroinflammation-and degeneration-related diseases.…”
Section: Discussionmentioning
confidence: 99%
“…LPS administration induced depression-like behaviors, triggered microglial activation in the hippocampus, and upregulated proinflammatory cytokine expression (Brites and Fernandes, 2015). Activated microglia are the major source of proinflammatory cytokines, such as TNF-a, IL-1b, and IL-6, in the CNS (Yang M. et al, 2018). Preclinical and clinical studies have proposed that proinflammatory cytokines are associated with the pathogenesis of depression (Karson et al, 2013) and that an increase in pro-inflammatory cytokines contributes to depressive-like behaviors (Raison et al, 2006;Guo et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The paradigm of forced swim test (FST) is based upon the evaluation of immobility, as a measure of behavioral despair in stressful and inescapable situations [13]. In brief, each rat was placed in a glass cylinder (45 cm height, 25 cm diameter) which contained approximately 35 cm of water (24 ± 1°C) for 15 min.…”
Section: Behavioral Testsmentioning
confidence: 99%